2007
DOI: 10.1124/jpet.106.115840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of (R)-2-(2-Aminothiazol-4-yl)-4′-{2-[(2-hydroxy-2-phenylethyl)amino]ethyl} Acetanilide (YM178), a Novel Selective β3-Adrenoceptor Agonist, on Bladder Function

Abstract: We evaluated the pharmacological characteristics of (R)-2-(2-aminothiazol-4-yl)-4Ј-{2-[(2-hydroxy-2-phenylethyl)amino]-ethyl} acetanilide (YM178). YM178 increased cyclic AMP accumulation in Chinese hamster ovary (CHO) cells expressing human ␤ 3 -adrenoceptor (AR). The half-maximal effective concentration (EC 50 ) value was 22.4 nM. EC 50 values of YM178 for human ␤ 1 -and ␤ 2 -ARs were 10,000 nM or more, respectively. The ratio of intrinsic activities of YM178 versus maximal response induced by isoproterenol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
209
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(228 citation statements)
references
References 25 publications
8
209
4
1
Order By: Relevance
“…In human embryonic kidney (HEK) cells stably transfected with human β 3 -adrenoceptors at a density of 121-fmol/mg protein, mirabegron and isoprenaline exhibited apparent affinities of 55 nM and 34 μM, respectively, in competition radioligand binding studies, and these affinities were not substantially altered in HEK cells transfected with several naturally occurring gene variants of the receptor ). In cyclic AMP accumulation experiments in these HEK cells, mirabegron and isoprenaline exhibited EC 50 values of 0.93 and 11.2 nM, respectively, and the efficacy of mirabegron relative to isoprenaline was 0.85, which is in good agreement with the findings in CHO cells (Hatanaka et al 2013b;Takasu et al 2007). The potency and efficacy of mirabegron also was not affected by genotype in these experiments.…”
Section: Biochemical and Cellular Studiessupporting
confidence: 80%
See 3 more Smart Citations
“…In human embryonic kidney (HEK) cells stably transfected with human β 3 -adrenoceptors at a density of 121-fmol/mg protein, mirabegron and isoprenaline exhibited apparent affinities of 55 nM and 34 μM, respectively, in competition radioligand binding studies, and these affinities were not substantially altered in HEK cells transfected with several naturally occurring gene variants of the receptor ). In cyclic AMP accumulation experiments in these HEK cells, mirabegron and isoprenaline exhibited EC 50 values of 0.93 and 11.2 nM, respectively, and the efficacy of mirabegron relative to isoprenaline was 0.85, which is in good agreement with the findings in CHO cells (Hatanaka et al 2013b;Takasu et al 2007). The potency and efficacy of mirabegron also was not affected by genotype in these experiments.…”
Section: Biochemical and Cellular Studiessupporting
confidence: 80%
“…Two studies on CHO cells transfected with human β-adrenoceptor subtypes were reported with rather similar results. Thus, mirabegron stimulated cyclic AMP accumulation via β 3 -adrenoceptors with EC 50 values of 22 nM (Takasu et al 2007) and 1.5 nM (Hatanaka et al 2013b), its efficacy relative to isoprenaline was 0.8 in both studies; in contrast, efficacy at human β 1 -and β 2 -adrenoceptors was only 0.1-0.2 in both studies, which did not allow quantification of potency. In human embryonic kidney (HEK) cells stably transfected with human β 3 -adrenoceptors at a density of 121-fmol/mg protein, mirabegron and isoprenaline exhibited apparent affinities of 55 nM and 34 μM, respectively, in competition radioligand binding studies, and these affinities were not substantially altered in HEK cells transfected with several naturally occurring gene variants of the receptor ).…”
Section: Biochemical and Cellular Studiesmentioning
confidence: 88%
See 2 more Smart Citations
“…b 3 -AR selective agonists are currently being evaluated as potential treatment for OAB in humans. 125 One of these, YM187, which mediated muscle relaxation in human bladder strips, 126 was given to patients with OAB in a controlled clinical trial. 127 The primary efficacy analysis showed a statistically significant reduction in mean micturition frequency Neurourology and Urodynamics DOI 10.1002/nau compared to placebo.…”
Section: 105mentioning
confidence: 99%